Estimation of Heavy Metals in Multivitamin Tablets by Differential Pulse Anodic Stripping Voltammetry - Kumar Rohit Raj; Shashank Sharma; Sachin Saxena; M. M. Srivastava; Soami P. Satsangi (E-Journal of Chemistry)
Differential pulse anodic stripping voltammetry (DPASV) was applied for the simultaneous determination of zinc and copper in multivitamin tablet (supradyn and centrum). Determination of the metals was made in ammonium acetate buffer (pH 4.5) with a scan rate of 0.01 V/s by Hanging Mercury Dropping Electrode (HMDE).The solution was stirred during electrolysis at -1.3 V for 300 s in the potential range of -1.3 to + 0.1 V. Concentrations of zinc and copper in supradyn drug sample were found to be 1.80 and 2.9 mg/tablet and for centrum drug sample were found to be 4.6 and 0.94 mg/tablet respectively.